Patient education for HIV-infected patients: a tool for success. Issue 2 (12th March 2012) - Federspiel, F.; Coleou, J.; Adda, A.; Traore, K.; Slama, L.; Debrix, I.; Pialoux, G.; Guessant, S.
Abstract : Background: Patient education (PE) is a discipline supported by the current legislation in France. A PE programme has been set up at Tenon Hospital (Paris, France) by pharmacists and nurses for patients infected with HIV. Purpose: The aim of this study was to assess the programme in terms of virological efficacy among patients referred to PE between 2009 and 2010 for treatment initiation or failure. Materials and methods: The last available plasma viral load (VL) dating from at least 6 months after starting treatment or last change of treatment was recorded for each patient followed in PE. The proportion of patients with virological suppression, that is having an undetectable VL at the threshold of 50 copies per mL, was then compared to that observed under the same conditions on all patients treated by the Infectious and Tropical Diseases Department (ITD) in 2010 and who were not referred for PE. Results: 63 patients were followed between 2009 and 2010 in the PE program. 86.0% of them (43/50) were in virological success after at least 6 months of therapy. This rate is comparable to the 86.1% (1979/2297) of patients with virological suppression from the active list of patients followed at ITD and who have not benefited from PE. At the beginning of PE, 38% (8/21) of pretreated patients were undetectable; to date, they are 81% (17/21) with virological suppression (p <0.01). These preliminary results suggest that among patients in therapeutic failure or having adherence difficulties, the PE program provides outcomes comparable to those observed in the active list. Conclusions: These encouraging results enable us to prepare a prospective, comparative, randomised study to confirm them and to consider new end points such as patient satisfaction, quality of life and the expected benefits in terms of reduced costs thanks to the PE program.